„Es gibt ja Zeichen für Wörter...". Grammatisches und Zeichenhaftes in Sprach(en)repertoires entdecken - Topalović, Elvira; Härtel, Kira (Die Grundschulzeitschrift)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

The Cost of Tax Simplification: Evidence from Risk-taking in a Turnover-based Corporate Tax System - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Umfrage: Beurteilung Investitionsfördernder Maßnahmen durch Unternehmen im Handwerk - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Interval incremental learning of interval data streams and application to vehicle tracking - Leite, Daniel; Škrjanc, Igor; Blažič, Sašo; Zdešar, Andrej; Gomide, Fernando (Information Sciences)

Data Driven Fuzzy and Neural Dynamic Systems Modeling - Leite, Daniel; Gomide, Fernando (2023 International Conference on Machine Learning and Cybernetics (ICMLC))

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas Manuel; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (LWDA’23: Learning, Knowledge, Data, Analysis.)

Telecom C-band photon emission from (In,Ga)As quantum dots generated by filling nanoholes in In0.52Al0.48As layers - Deutsch, Dennis; Buchholz, C.; Zolatanosha, V.; Jöns, K. D.; Reuter, Dirk (AIP Advances)
We present the fabrication of strain-free quantum dots in the In0.53Ga0.47As/In0.52Al0.48As-system lattice matched to InP, as future sources for single and entangled photons for long-haul fiber-based quantum communication in the optical C-band. We achieved these quantum dots by local droplet etching via InAl droplets in an In0.52Al0.48As layer and subsequent filling of the holes with In0.53Ga0.47As. Here, we present detailed investigations of the hole morphologies measured by atomic force microscopy. Statistical analysis of a set of nanoholes reveals a high degree of symmetry for nearly half of them when etched at optimized temperatures. Overgrowth with 50–150 nm In0.52Al0.48As increases their diameter and elongates the holes along the [01̄1]-direction. By systematically scanning the parameter space, we were able to fill the holes with In0.53Ga0.47As, and by capping the filled holes and performing photoluminescence measurements, we observe photoluminescence emission in the O-band up into the C-band depending on the filling height of the nanoholes.

Ein praxisorientiertes Zusammenspiel von Psychomotorik und Tanzimprovisation - Scholz, Maren; Gabriel, Lena (sportpädagogik)

Tanzen, Rhythmus, Darstellen. Die große Spielesammlung - Gabriel, Lena; Teubert, Hilke (Wimasu)

Deciding Subsumption in Defeasible 𝓔𝓛𝓘⊥ with Typicality Models - de Camargo e Souza Câmara, Igor; Turhan, Anni-Yasmin (Logics in Artificial Intelligence)

Ästhetik digitaler Medien. Aktuelle Perspektiven - Flath, Beate (mediendiskurs 17)

Von der "Shallowing Hypothese" zur "Illusion of Understanding" -wie wirken Erklärvideos und Lehrbuchtexte auf Wissen und Verstehensillusion? - Kulgemeyer, Christoph; Sterzing, Fabian Gabriel; Hörnlein, Madeleine

"Aus Erklärvideos lernt man nur oberflächlich" - oder erwirbt man auch Konzeptwissen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian Gabriel; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Sprachlichkeit des Geschichtslernens. Fachliche Grundlagen, Sprachgebrauch und Ansätze fachintegrierter Spracharbeit - Hartung, Olaf (Beiträge zur Lehrerinnen- und Lehrerbildung)

Designing Self-Regulation interventions for different target groups in Entrepreneurship Education - Jenert, Tobias; Büker, Ronja (20th Biennial EARLI Conference)

Selbstregulation von Unternehmer*innen - eine latente Klassenanalyse - Büker, Ronja; Bellwald, Noah (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)